Protected geographical indication recognition and willingness to pay: A case of grojec apple - Ahrendsen, Bruce L.; Majewski, Edward (Applied Studies in Agribusiness and Commerce, 2017)
The Grojec region of Poland is an important region for apple production and accounts for 40 percent of domestic apple production. Apple growers from the region made an attempt to strengthen their competitive position through registering their apples as Protected Geographical Indication (PGI) products. The European Commission’s PGI allows food producers to obtain market recognition and a premium price for their products. Although the Grojec Apple received PGI registration in 2011, little has been done to promote apples with the PGI label. Two important research questions are addressed: 1) Does the Polish market recognize Grojec Apple PGI, and 2) Does the market value Grojec Apple PGI? Logit and regression models are estimated using survey data collected during an International MBA in Agribusiness and Commerce study week in Warsaw. Only 22% of consumers recognize Grojec Apple PGI. Yet, 70% of consumers indicate they are willing to pay more for the product and their average willingness to pay (WTP) premium is 32%. Results indicate use of the PGI label may be effective in improving sales and profit margins for Grojec Apple producers and their affiliated cooperatives. Older consumers are more likely to indicate a WTP premium. Males, smaller households, and consumers less sensitive to apple price indicate a higher WTP premium. An advertising campaign promoting Grojec Apple PGI as a better product may be effective at increasing consumer likelihood to pay more and WTP premium. Although “Grojec” is already familiar to most consumers in central Poland as a region for apples, a Grojec Apple with PGI label would assure consumers they are purchasing apples from the Grojec region and the apples are high quality.JEL Code: D12, Q13, Q18